Analysis of Current Carrying Capacity of Power Cable Based on DTS. (October 2020) - Yaodong, Zhang; Yi, Kan; Xiaopo, Mao; Xueming, Zhou; Zhiqiang, Feng; Zeqi, Huang; Xiang, Ren; Tianru, Shi; Jianjin, Fu; Junjie, Huang
Abstract: This article uses a distributed optical fiber temperature measurement system (DTS, Distributed Temperature Sensing) to fix the temperature measurement optical fiber on the surface of the power cable, collect the real-time operating temperature of the power cable, conduct the ampacity test, and analyze the cable laying method and depth, soil temperature, Soil thermal resistance coefficient, cable spacing and irradiation strength and other test conditions, the impact on the current carrying capacity of power cables. According to the real-time monitoring temperature of the cable, the alarm can be made when the cable temperature is too high or the temperature rise speed is too fast. And on the basis of determining the working temperature and load operating conditions of the cable conductor core, dynamically calculate the current carrying capacity of the cable, which is conducive to improving the performance of the power cable and increasing the load capacity of the power cable.